Gut microbiota-regulated bile acids metabolism features in the aging process in mice - Kechun CHEN; Yating ZHAO; Lexun WANG; Yifan YIN; Ling YANG; Duosheng LUO (KeAi Communications Co., Ltd., 2022)
Objective: Aging is typically characterized by imbalanced gut microbiota and bile acid (BA) dyshomeostasis. However, features of the gut microbiota-regulated BA metabolism in the aging process remain unclear. Aim: To establish a direct link between gut microbiota and BA profile changes in the liver, plasma, and intestinal contents and to further understand aging and aging-related diseases from the liver-gut axis. Methods: The BA content in the liver, plasma, and intestine were determined using ultra-performance liquid chromatography-tandem mass spectrometry. Gut microbiota were sequenced by 16S rDNA, and the expression of the liver-gut axis-related proteins was detected. Results: The plasma content of total cholesterol, triglycerides, and low-density lipoprotein cholesterol gradually increased during aging, and Lactobacillus, Bacteroides, Bacillus, Ruminococcus, Blautia, and Streptococcus, which can produce bile salt hydrolase, were increased. The concentration of total BAs was increased, especially that of unconjugated BAs, and the ratio of unconjugated BAs to conjugated BAs was also increased. The expression of bile acid transporter receptors and intestinal tight junction proteins was significantly decreased. Conclusion: The presented data show that the changes in BA profile mediated by gut microbiota were closely related to aging and highlights that more attention should be paid to targeting gut microbiota-regulated BA metabolism to prevent and treat aging-related diseases, especially lipid metabolism disorders.